“Alquería Traca Traca” immersive and multisensory farce for the blind: Re-aproximación humana entre mascarillas por la COVID-19 - Verdesoto, Irina (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
“Alquería Traca Traca” is the update of a Valencian farce to an immersive and multisensory show. The objectives will analyze the reapproach to face-to-face theater in 2021, and will identify proxemic relationships, social distancing, and the use of masks. The methodology deploys the literary artistic chronotype theory in three parts and applies eight proxemic dimensions. As a result, the reapproach takes place slowly and coexists with the blind person, her companion, the guide-narrator and the technical support team. The immersive and multisensory elements of the development of the plot have been effective, but among all of them, the conversation, the accompaniment, the dialogue, talking and tasting slowly together with the blind stand out.